Lifestyle behaviors among 4,343 Brazilian adults with severe mental illness and 55,859 general population controls: Data from the Brazilian national health survey - Werneck, André O. [UNESP] (2020)
Objective: To analyze the association between severe mental illnesses and health behaviors among Brazilian adults. Methods: We used data from the Brazilian National Health Survey, a large nationally representative cross-sectional study conducted in 2013 among 60,202 adults (≥ 18 years). Clinical diagnoses (major depressive disorder, bipolar disorder and schizophrenia), lifestyle behaviors (leisure-time physical activity, TV viewing, tobacco use and the consumption of alcohol, sweets, and soft drinks) and potential confounders (chronological age, race, educational and employment status) were self-reported. Logistic regression models were used to examine the associations between severe mental illness and lifestyle behaviors, adjusting for confounders. Results: Schizophrenia (n=41) was associated with lower odds of physical activity (OR 0.08 [95%CI 0.01-0.58]). Major depressive disorder (n=4,014) was associated with higher odds of TV viewing (OR 1.34 [95%CI 1.12-1.61]), tobacco use (OR 1.37 (95%CI 1.18-1.58]), consumption of sweets (OR 1.34 (95%CI 1.15-1.55]) and consumption of soft drinks (OR 1.24 (95%CI 1.06-1.45]). There were no significant associations between bipolar disorder (n=47) and any lifestyle behaviors. Conclusions: Schizophrenia was associated with lower physical activity, while major depressive disorder was associated with increased TV viewing, tobacco use, and consumption of sweets and soft drinks. These findings reinforce the need for prevention and treatment interventions that focus on people with severe mental illness in Brazil.